Factors of sustainable competitiveness at company level: a comparison of four global economic sectors - Șerban, Radu-Alexandru; Mihaiu, Diana Marieta; Țichindelean, Mihai; Ogrean, Claudia; Herciu, Mihaela (Journal of Business Economics and Management, 2023)
Built on the premise that a company’s competitiveness is given by its robust financial performance and the strength of its position on the market, but only under conditions of sustainability, this study aims to investigate the key factors of company competitiveness while considering sustainability issues. The two research objectives were: (1) to identify and analyze the key factors of sustainable competitiveness at company level (2) to find sector-related discrepancies regarding the identified factors. To achieve them, a horizontal analysis covering ten financial years (2012–2021) was performed on a sample of 1,449 companies from four global economic sectors (Consumer Cyclicals, Energy, Health Care, and Technology) – using Exploratory factor analysis (EFA) and ANOVA. Nine factors (both financial and non-financial) were found: liquidity, profitability, revenue efficiency, inventory management efficiency, ESG performance, receivables management efficiency, R&D efficiency, book value, and market value. Of them, ESG performance has emerged as an independent factor based on non-financial variables, its introduction into the research model being one of the study’s novelties. Significant mean differences were found between the nine factors, depending on the sector, which allowed the ranking of sectors in terms of sustainable competitiveness, in descending order: Health Care, Technology, Consumer Cyclicals, and Energy.